Comparison of the Effectiveness of Cognitive Behavioral Therapy and Schema Therapy on Cognitive Emotion Regulation in Patients with Major Depressive Disorder - Barooti, Mahshid; Chinaveh, Mahboobeh; Saedi, Sara (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The aim of this study was to compare the efficacy of cognitive behavioral therapy and schema therapy on cognitive emotion regulation in patients with major depressive disorder.Methods and Materials: The research employed a quasi-experimental pre-test-post-test design with a control group and a one-month follow-up. The study population included all patients visiting Entekhab-e No and Aryaz clinics in Tehran during the period from February 2021 to May 2021, who were diagnosed with major depressive disorder by a psychiatrist. Forty-five individuals were purposively selected and randomly assigned to two experimental groups and one control group (15 per group). The first and second experimental groups underwent 12 and 8 sessions of cognitive behavioral therapy based on the Rosello protocol (2015) and schema therapy based on Young's protocol (2003), respectively. The research instrument was the Cognitive Emotion Regulation Questionnaire (CERQ) (Garnefski & Kraaij, 2006). Data were analyzed using repeated measures ANOVA, Bonferroni test, and SPSS version 24.Findings: Results showed that both cognitive behavioral and schema therapy interventions significantly improved scores of adaptive emotion regulation and decreased scores of maladaptive emotion regulation compared to the control group (P